Investigation of inner mechanism of anisotropic mechanical property of antler bone. (December 2018) - Fang, Zhongqi; Chen, Bin; Lin, Shiyun; Ye, Wei; Xiao, Hang; Chen, Xi
Abstract: Bones have different functions and various applications depending on the roles they play in different mammal bodies. The internal relationships between the functions and microstructures of bones need further expounding to understand their specific mechanical properties. In this study, the relationships between the mechanical properties and microstructures of the compact bone of antler (called as antler bone for short) along its three different orientations are investigated. First, the bending mechanical properties of the specimens of the antler bone along its three different orientations are tested with material-testing machine, followed by the observations of the crack-extending routes and the fracture surfaces of the three different orientations with a scanning electron microscope (SEM). The results of the tests reveal that the antler bone possesses anisotropic mechanical property. Namely, the mechanical properties of the antler bone are closely related to its orientations. Concretely, the fracture strength, elastic modulus and work-of-fracture along the transversal orientation of the bone are remarkably larger than those of the longitudinal and radial orientations. The results of the observation of the SEM show that there are different crack-extending routes and fracture-surface characteristics along the three different fracture orientations of the bone. Specifically, there are crack deflections and crack twists along the transversal fracture orientation, crack bridging along the longitudinal fracture orientation and crack rounding of osteons along the radial fracture orientation. Based on the tested and observed results, the fractal models of the crack-extending routes along the three different fracture orientations are presented. The fractal dimensions and critical crack extension forces along the three different fracture directions are calculated based on the fractal models. Further, the box-counting method is adopted to verify the correctness of the models. It is indicated that the fractal dimension and fracture energy of the transversal orientation are obviously larger than those of the longitudinal and radial orientations, which are in accordance with the experimental results.